Analisis Konsentrasi Pestisida Klorpirifos pada Letal Ikan Mas (Cyprinus carpio) - Rohimah, Ririn Alfiatu; Santoso, Hari; Syauqi, Ahmad (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2024)
One type of orghanophosphate pesticide used by farmers is chlorpyrifos. Uncontrolled use of pesticides has an impact on environmental pollution, especially aquatic biota. The purpose of this study was to analyze the acute concentration of chlorpyrifos pesticide against goldfish (Cyprinus carpio). The research method was experimental with preliminary research, acute toxicity test (LC50), real test (sub lethal). The concentration of treatment in experimental animals includes the sublethal test K0 (control) 0 ppm, K1 0.25 ppm, K2 0.30 ppm, K3 0.35 ppm, K4 0.40 ppm, K5 0.45 ppm. The preliminary test results obtained an upper lethal threshold value of 0.5 ppm and a lower lethal threshold value of 0.25 ppm. Acute toxicity tests ranged from K1 0.25 ppm to K5 0.45 ppm. The results of the acute toxicity test (LC50) at K1 0.25 ppm and K2 0.30 ppm showed experimental goldfish exposed to chlorpyrifos experienced abnormal behavior, namely increased operculum movement (opening and closing) with an average of K1 = 72.405; K2 = 43.130 causes goldfish to die quickly, swim on the surface, tend to approach the aerator, and move quickly without direction. The conclusion is that there is a significant relationship between the amount of pesticide concentration given to the survival of goldfish. Keywords:Goldfish (Cyprinus carpio), Chlorpyrifos pesticide